10.1 OPTIMAL AUTOMATED UNOBSERVED OFFICE BLOOD PRESSURE PROTOCOL: ONLY 6-MINUTES AND TWO READINGS MAY BE NEEDED - Myles Moore; Nathan Dwyer; Ella Hoban; Mark Nelson; Dean Picone; Martin Schultz; James Sharman (Artery Research, 2016)
Background: Automated office blood pressure (AutoBP) involving repeated, unobserved blood pressure (BP) readings during one clinic visit provides a practical alternative to daytime ambulatory blood pressure (ABP). However, the number of reading taken and measurement duration have varied across previously used AutoBP protocols. Therefore, the optimal AutoBP protocol taken in the least amount of time with the fewest BP readings is yet to be determined and was the aim of this study. Methods: 117 patients (mean age 61.5±12.5 years) referred to a specialist BP clinic underwent AutoBP in a quiet room alone. Eight BP measurements were taken at 2-minute intervals immediately after sitting. The optimal AutoBP protocol with the highest concordance to daytime ABP was defined by smallest mean difference and highest intra-class correlation coefficient (ICC). The same BP device (Mobil-o-graph, IEM) was used for both AutoBP and daytime ABP. Results: Average 15-minute AutoBP and daytime ABP were 138.4±18.1/84.8±12.2 mmHg and 140.9±15.2/86.2±10.6 mmHg, respectively. The AutoBP protocol with the highest concordance to daytime ABP was the average of two measures taken between two and six minutes of seated rest (systolic BP: mean difference = 0.3 (95%CI -3.0,2.4) mmHg, p=0.84; ICC=0.80; diastolic BP: mean difference = −0.42 (95%CI -2.0,1.1) mmHg, p=0.60; ICC=0.85). Daytime ABP tended to be overestimated by individual and the average of more than one AutoBP recorded before six minutes, however daytime ABP was underestimated after this time. Conclusion: Only six minutes and two AutoBP readings may be needed to be comparable with daytime ABP.